2006
DOI: 10.1248/bpb.29.467
|View full text |Cite
|
Sign up to set email alerts
|

Scavenging of Reactive Oxygen Species by Eriobotrya japonica Seed Extract

Abstract: We have clarified that Eriobotrya japonica seed extract has strong antioxidative activity, and is effective for the prevention and treatment of various diseases, such as hepatopathy and nephropathy. In this study, to investigate the influences of components of Eriobotrya japonica seed extract on its antioxidative activity, extracts were prepared using various solvents (n-hexane (Hex), ethyl acetate (EtOAc), n-butanol (n-BuOH), methanol (MeOH) and H 2 O) and the antioxidative activity of the solvent fractions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 23 publications
(21 reference statements)
2
42
0
1
Order By: Relevance
“…According to literature data, phenol compounds in plants are the largest group of compounds with antioxidative properties (10,14). For this reason we found it expedient to determine the total amount of phenol compounds in the investigated tinctures (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…According to literature data, phenol compounds in plants are the largest group of compounds with antioxidative properties (10,14). For this reason we found it expedient to determine the total amount of phenol compounds in the investigated tinctures (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There is a relationship between antioxidant activities and the contents of total phenolics or flavonoids. Also, Yokota et al [34] reported scavenging activity of ROS by Eriobotrya japonica seed extracts. Scavenging of H 2 O 2 by EJFE may be attributed to their phenolic compounds (gallic acid) which can donate electrons to H 2 O 2 , neutralizing it to H 2 O and O 2 .…”
Section: Modeling Of Mercury Accumulation In Liver Tissuesmentioning
confidence: 99%
“…Eriobotrya japonica flower extracts as an antioxidant agent ameliorated oxidative stress in these tissues (see Figure 2). Based on research of Yokota et al [34] Eriobotrya japonica seed extracts have strong antioxidative activities, lipid peroxidation inhibition activities, and are effective for the prevention and treatment of various diseases such as hepatopathy and nephropathy. Also, incubation with ethanol extract of loquat (Eriobotrya japonica) seeds significantly lowered the TBARS levels [36].…”
Section: Modeling Of Mercury Accumulation In Liver Tissuesmentioning
confidence: 99%
“…Antidiabetic activity has been reported from the leaves of this plant. [11][12][13][14][15][16] . Very less work has been done on the fruit and seeds of this plant.…”
Section: Introductionmentioning
confidence: 99%